Studies on the Effect of Ethylmethane Sulphonate on Eucalyptus tereticornis X E. camaldulensis for Evolving Mutation Breeding Methods - Swarup, K. M. Renu; Kapoor, M. L. (Indian Forester, 1984)
Air dry and pre-soaked seeds of Eucalyptus (FRI-4) were treated with ditrerent concentrations of Ethylmethane sulphonate (EMS) for framing methods and technique for mutation breeding programme. The effect of EMS was assessed on the basis of different parameters viz. Germination, Germination value, Hypocotyl and Radicle length, Cotyledon length and width, Green and Dry weight and Chromosomal abnormalities at anaphase. Air-dry seeds were found to be more sensitive to EMS in comparison to pre-soaked seed. Stimulation was observed in a few parameters at low concentrations. Germination value, radicle length and mitotic divisions were found to be the most sensitive parameters. These findings will be very useful for guiding mutation breeding work in tree species.